The Implementation of Newmarkâ€™s Translation Procedures in Colours Magazine to Achieve Grammatical Equivalence - Benedikta Andriela Yuni Seran; Rudi Hartono; Januarius Mujiyanto (Universitas Negeri Semarang, 2022)
â€œColours Magazineâ€ is an official monthly publication magazine of Garuda Indonesia Airlines. It is a bilingual magazine written in English and Bahasa Indonesia. This study aims to analyze the implementation of Newmarkâ€™s translation procedures and its resulting grammatical equivalence between the source text (ST) and target text (TT). This study focused on the implementation of (1) the transference procedure; (2) the naturalization procedure; (3) the cultural equivalent procedure; (4) the synonymy procedure; (5) the modulation procedure; (6) the couplets procedure; (7) the grammatical equivalence achievements through the use of those procedures. This research employed a descriptively qualitative approach. The study findings reveal that transference is the most dominant procedure, which is used 61 times. Couplets are the second rank which has been used 36 times. The cultural equivalent is used 24 times and the naturalization procedure 14 times. At the same time, modulation is used 11 times and 13 times for synonymy. On the other hand, the researchers also found that implementing six translation procedures has resulted in 82 number equivalents, 126 tense equivalents, and 125 voice equivalent sentences. 25 non-equivalent sentences in the number category happened because there are different habits of delivering singularity and plurality between ST and TT. In the tense grammatical category, there are 10 non-equivalent sentences caused by different rules between the source and target languages. While in the voice category, there are 8 non-equivalent sentences caused by the changing of the words, the use of specific terms, and the changing of subject position.